﻿Retour aux traditions — signe de réussite sociale : les rondels de la Collection Hosmer (Université McGill, Montréal) - Isler-de Jongh, Ariane (RACAR : Revue d'art canadienne / Canadian Art Review, 1989)
The collection of domestic stained glass and glass paintings recently set up in the new building of the McGill School of Architecture used to decorate the main staircase and the dining-room windows of Charles Hosmer’s house, built by Montreal architect Edward Maxwell around the turn of the century.Charles R. Hosmer was then a prominent businessman, the head of Ogilvie Flour Mills, and his house on Drummond Street was a sign of his position in the flourishing city of 1900. It was to be the house of an art collector, who was interested in paintings as well as in “objets d’art,” which he would buy himself or through agents. Indeed we know from Maxwell’s ledgers that these glass paintings were acquired as a group from a London dealer of Flemish or Dutch origin, Martin van Straaten.This collection of 39 small domestic glass panels, of varied quality and origins, comprises Flemish and Dutch roundels, piecess from the Rhineland and Switzerland, and some heraldic panels. This type of glass used to adorn windows of wealthy houses, private chapels or cloisters. The roundel itself is a single piece of colourless glass, circular, oval or rectangular, painted with grisaille and silver-satin and occasionally, after the sixteenth century, with coloured enamels. The Swiss panels, on the other hand, consist of a main piece in the centre, richly framed with decorative and allegorical subjects.McGill’s Hosmer Collection is, as far as we know, unique in Canada. In acquiring it, Charles Hosmer followed the lead of British collectors, who had been keenly interested in northern European domestic glass, at least since the eighteenth century. These small panels are of average quality, although some of them are outstanding. As a group, they present a remarkable anthology of styles and techniques in the sixteenth and seventeenth centuries, as well as examples of nineteenth-century repairs or even pastiches. The catalogue consists of a check-list according to the Corpus vitrearum norms (thus representing the first contribution to the Canadian C.V.), accompanied by detailed notices describing the current state of research.